Analisis Faktor Yang Berhubungan Dengan Self Efficacy Manajement Obesitas Pada Mahasiswa Fakultas Kesehatan Universitas Muhammadiyah Sukabumi - Ekowatiningsih, Dyah (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2024)
Obesity is a condition where there is an accumulation of excess body fat so that a person's weight is far above normal and can endanger health. Obesity management will provide optimal results, if the person does diet, physical activity, and behavior therapy seriously. Therefore, strong self-efficacy is needed to get maximum results. The purpose of this study is to analyze factors related to self-efficacy obesity management in students of the Faculty of Health, University of Muhammadiyah Sukabumi. The sampling determination technique uses probability sampling with a sample size of 83 students. This study uses a descriptive-analytical method with a cross-sectional design. Data collection was carried out by interviews, surveys and questionnaire distribution. The data analysis technique used is logistic regression. The results of this study found that Attitude with P value: 0.001 (< 0.05), Physical and Emotional Conditions with P value: 0.001 (< 0.05), and Gender with P value: 0.032 (< 0.05) had a significant relationship with Self Efficacy in Student Obesity Management, Faculty of Health, University of Muhammadiyah Sukabumi. Efforts to improve self-efficacy in obesity management are by improving body condition, decreasing stress, and being ready to undergo a diet. This research is expected to be used as a reference material, providing information and understanding to students about factors related to obesity self-efficacy.